2015
DOI: 10.1074/jbc.m115.686261
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Two Human Skeletal Calsequestrin Mutants Implicated in Malignant Hyperthermia and Vacuolar Aggregate Myopathy

Abstract: Background: Hereditary mutations (D244G and M87T) of skeletal calsequestrin have been associated with skeletal myopathies. Results: The D244G mutation loses Ca 2ϩ , resulting in structural instability. M87T inhibits polymerization of calsequestrin by altering the Casq1 dimer interface. Conclusion: D244G is largely dysfunctional, whereas the Ca 2ϩ binding capacity of M87T is mildly reduced. Significance: Altered characteristics of Casq1 mutants are congruent with their associated disease phenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(68 citation statements)
references
References 24 publications
11
57
0
Order By: Relevance
“…Buffering power B, the incremental ratio of bound over free ligand concentration, is maximal at zero ligand concentration, when the buffer is ligand-free, for most buffers. The buffering power of calsequestrin measured in vitro instead increases with the concentrations of free and bound calcium (6). This increase in buffering ability occurs because the loci for most calcium binding are at the interfaces between calsequestrin monomers, requiring two monomers to achieve useful binding affinity (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Buffering power B, the incremental ratio of bound over free ligand concentration, is maximal at zero ligand concentration, when the buffer is ligand-free, for most buffers. The buffering power of calsequestrin measured in vitro instead increases with the concentrations of free and bound calcium (6). This increase in buffering ability occurs because the loci for most calcium binding are at the interfaces between calsequestrin monomers, requiring two monomers to achieve useful binding affinity (12).…”
mentioning
confidence: 99%
“…Depolymerization would derail the hypothetical diffusional enhancement by destroying the calcium wires; it might also allow migration of calsequestrin away from triads, with damaging targeting and functional repercussions. Finally, all calsequestrin mutations associated with diseases of skeletal muscle (6) and many of the known calsequestrin mutations linked to cardiac diseases (17) are known or predicted to alter its polymerization; therefore, it can be anticipated that any changes that hinder normal polymerization of this protein [including the posttranslational modifications recently studied (18)]…”
mentioning
confidence: 99%
“…17; a full list is included in supplemental Table 1). These proteins with highly charged binding sites share common biological functions for conformational switching or calcium titration; for example, calsequestrin (58), human Hsp70 (59), and an Na ϩ /Ca 2ϩ exchanger binding domain (60) have a similarly high charge density binding pocket as Protein S. Many of these proteins with exceptionally electronegative binding sites have already been reported to harbor great structural instability in the absence of calcium (54,55,(57)(58)(59)(60)(61)(62) or have increases in folding speed due to calcium (63). Because many of these proteins are also multidomain, our results on Protein S may apply to many of the proteins with high charge density sites.…”
Section: Discussionmentioning
confidence: 99%
“…From a functional point of view, muscle fibers isolated from these patients show (i) decreased Ca 2+ release following caffeine administration, (ii) increased glycogen content and misoriented SR junctions, (iii) an increase by approximately 25% of calsequestrin 1 content and (iv) a lower content of polymerized calsequestin [35,73]. Interestingly a report on the physicochemical properties of wild type and p.D244G mutated CASQ1 showed that the mutation reduces the Ca 2+ binding properties of calsequestrin 1 and causes it to form large aggregates in vitro [36]. It should be pointed out that all the patients identified so far were heterozygous for the causative CASQ1 mutation, while the functional studies were performed on homozygous mutated calsequestrin 1 molecules.…”
Section: Casq1 Mutations and Vacuolar Aggregate Myopathymentioning
confidence: 98%
“…Two isoforms of calsequestrin have been identified: calsequestrin1 that is predominantly expressed in fast twitch skeletal muscles and calsequestrin 2 that is expressed in cardiac and slow twitch muscle. Mutations in CSQ2 (the gene encoding calsequestrin 2) have been linked to catecholaminergic polymorphic ventricular tachycardia (CPVT), sudden cardiac arrest and heart failure [33,34] and will not be discussed in this review, whereas mutations in CSQ1 (the gene encoding calsequestrin 1) have been implicated in rare cases of malignant hyperthermia and vacuolar aggregate myopathy [35,36].…”
Section: Excitation-contraction Couplingmentioning
confidence: 99%